Lower high-density lipoproteins levels during human immunodeficiency virus type 1 infection are associated with increased inflammatory markers and disease progression (2023)
Introduction: High-density lipoproteins (HDL) are responsible for the efflux and transport of cholesterol from peripheral tissues to the liver. In addition, HDL can modulate various immunological mechanisms, including the inflammatory response. Inflammasomes are multiprotein complexes that have been reported to be activated during human immunodeficiency virus type 1 (HIV-1) infection, thus contributing to immune hyperactivation, which is the main pathogenic mechanism of HIV-1 progression. However, the relationship between HDL and inflammasomes in the context of HIV-1 infection is unclear. Therefore, this research aims to explore the association between HDL and the components of the inflammatory response during HIV-1 infection. Methodology: A cross-sectional study, including 36 HIV-1-infected individuals without antiretroviral treatment and 36 healthy controls matched by sex and age, was conducted. Viral load, CD4+ T-cell counts, serum HDL, and C-reactive protein (CRP) were quantified. Serum cytokine levels, including IL-1ß, IL-6, and IL-18, were assessed by ELISA. The inflammasome-related genes in peripheral blood mononuclear cells were determined by quantitative real-time PCR. Results: HIV-1-infected individuals showed a significant decrease in HDL levels, particularly those subjects with higher viral load and lower CD4+ T-cell counts. Moreover, upregulation of inflammasome-related genes (NLRP3, AIM2, ASC, IL-1ß, and IL-18) was observed, notably in those HIV-1-infected individuals with higher viral loads (above 5,000 copies/mL). Serum levels of IL-6 and CRP were also elevated in HIV-1-infected individuals. Significant negative correlations between HDL and the mRNA of NLRP3, AIM2, ASC, IL-1ß, and IL-18, as well as viral load and CRP were observed in HIV-1-infected individuals. Likewise, a significant positive correlation between HDL and CD4+ T-cell counts was found. Conclusion: In summary, our results indicate that HDL might modulate the expression of several key components of the inflammasomes during HIV-1 infection, suggesting a novel role of HDL in modifying the inflammatory state and consequently, the progression of HIV-1 infection. © 2018 Marin-Palma, Castro, Cardona-Arias, Urcuqui-Inchima and Hernandez.